ANALISIS PERCEPATAN WAKTU PELAKSANAAN PROYEK BERBASIS MICROSOFT PROJECT (STUDI KASUS: PEMBANGUNAN RENOVASI HOTEL LAGUNA RESORT AND SPA NUSA DUA) - I GEDE NGURAH SUNATHA; TJOKORDA ISTRI PRAGANINGRUM; I PUTU SAI CANDRA PREMA NATA (GANEC SWARA, 2023)
In project construction, problems during the implementation phase are unavoidable, resulting in non-compliance with the previously designed plan. In the case study of the construction of the Laguna Resort and Spa Nusa Dua hotel, based on the author's observations, data from the Planned Time Schedule and Realization Time Schedule found differences in the realization time with the plan, where the realization was delayed. In overcoming the delay, it is necessary to accelerate the completion time by accelerating the implementation time and conducting an analysis regarding how much influence the acceleration of completion time has by utilizing the Microsoft Project program. The data used is a quantitative descriptive method, namely by submitting a request for data to the Contractor. From processing the data and conducting 3 experiments on Microsoft Project, the authors chose the second experiment, namely by accelerating the Millwork sub-bill by reducing the average work duration of 1 working day. Activities that experience acceleration are as many as 26 work items including 8 work items on the 1st floor, 6 items on the 2nd floor, 6 items on the 3rd floor, and 6 items on the 4th floor. The results of the accelerated time are 5 (days) according to the time plan schedule